IMPLEMENTATION OF THE KUA REVITALIZATION PROGRAM IN THE SOUTHEAST PONTIANAK DISTRICT RELIGIOUS AFFAIRS OFFICE - surkiya, surkiya; Herawati, Netty; Pudjianto, S.Y. (JPASDEV : Journal of Public Administration and Sociology of Development, 2024)
This research is entitled "Implementation of the KUA Revitalization Program at the Office of Religious Affairs in Southeast Pontianak District". This study aims to analyze the Factors Influencing the Implementation of the Sub-District KUA Revitalization Program at the Southeast Pontianak District Religious Affairs Office. The KUA Revitalization Program is an implementation of the Decree of the Minister of Religion Number 758 of 2021 concerning Revitalization of the District Religious Affairs Office. Revitalization of the sub-district KUA aims to improve religious services to the community and improve the quality of life for religious people. However, in reality the Revitalization of the Sub-district KUA at the Southeast Pontianak Sub-District KUA is not yet in accordance with the Decree of the Minister of Religion Number 758 of 2021 concerning Revitalization of the District Religious Affairs Office, so the author tries to analyze the factors that influence the implementation of the KUA Revitalization using George Edward III's theory. According to George Edward III, the factors that influence implementation consist of four variables, namely, communication, resources, disposition and bureaucratic structure. The author examined the KUA of Southeast Pontianak District using descriptive research with a qualitative approach. The recommendation from this research is that the Southeast Pontianak Subdistrict KUA must follow the technical guidelines for the revitalization of the Subdistrict KUA that have been established by the Ministry of Religion.  Keywords: revitalization, implementation, KUA